Ultrathin hematite photoanode with gradient Ti doping - Liu, Pengfei (2020)
The poor photoelectrochemical (PEC) performance derived from insufficient charge separation in hematite photoanode crucially limits its application. Gradient doping with band bending in a large region is then considered as a promising strategy, facilitating the charge transfer ability due to the built-in electric field. Herein, we developed a synthetic strategy to prepare gradient Ti-doped ultrathin hematite photoelectrode and systematically investigated its PEC performance. The as-synthesized electrode (1.5-6.0% doping level from the surface to the substrate) delivered a photocurrent of about 1.30 mA cm-2 at 1.23 V versus the reversible hydrogen electrode (RHE), which is nearly 100% higher than that of homogeneously doped hematite electrode. The enhanced charge transfer property, induced by the energy band bending due to the built-in electric field, has been further confirmed by electrochemical measurements. This strategy of gradient doping should be adaptable and can be applied for other functional materials in various fields.